STUDY ON GROWTH AND YIELD OF WATER SPINACH (Ipomoea reptans Poir) AGAINST GIVING OF SOME TYPES OF ORGANIC FERTILIZER AND N FERTILIZER - Simon Devlin Simangunsong; Elfin Efendi; Safruddin Safruddin (Universitas Asahan, 2018)
This research was arranged based on Factorial Randomized Block Design with two treatmentfactors and three replications, the first factor was the giving of various types of organic fertilizer(P) consisting of 4 levels ie P0 (without treatment), P1 (bokashi cow dung), P2 ( bokashi legum) and the second fator is the application of urea (U) fertilizer consisting of 3 levels ie U0 (control), U1 (10 g / plot) and U2 (20 g / plot). The results of research that treatment of various types of organic fertilizer significantly affect the growth and yield of water spinach. The best treatment was obtained at treatment (P3) yielding 22,10 cm height, 25,33 pieces of leaves, yield per crop 39,29 g and yield per plot 3,87 kg. The treatment of urea fertilizer has an effect on the growth and yield of spinach water. The best treatment was obtained at a dose of 20 g / plot (U2) resulting in plant height of 22.42 cm, number of leaves of 23.42 pieces, production per plant 39.04 g and production per plot of 3.85 kg. Interaction treatment of various types of organic fertilizers and urea fertilizers did not show a significant effect on the growth and yield of water spinach.